Teaching business ethics in a digital world. Issue 4 (4th September 2020) - Magrizos, Solon
Abstract : Purpose: While teaching of business ethics has been increasing in business schools worldwide, universities still face increasing pressure to do more to proactively defend and help avoid unethical business practices and scandals calling for more responsible education. This study aims to examine teaching business ethics in light of recent technological advances (i.e. teaching via the use of digital devices) and well-established pedagogical practices. Design/methodology/approach: This study uses a 2 × 2 experimental design examining the effect of active (vs passive) and presence (vs absence) of digital devices in student learning of 192 US students. Findings: The findings suggest that the active learning scenario, the usage of laptops and phones helped students get higher results in the test compared to active learning with no digital devices or passive learning with digital devices. Originality/value: Active learning practices such as group discussions and peer assessment or the flipped classroom approach make a difference for business ethics teaching where students need to develop inquiry and interest for the subject and engage in ethical dilemmas and real-life examples. Further, students in the active learning scenario performed better in knowledge tests when they were asked to use their digital devices.